The Cloning, Characterisation and Antisense Cassettes Construction for Some Pigmentation Genes from Oncidium SPP. - Manickam, Sugumaran (2000)
Genes that are responsible for color formation within the anthocyanin and carotenoid biosynthesis pathway have been isolated, studied and manipulated to produce novel colors in many plant species. Therefore, in this study, the genes that are involved in flower color formation namely CHS, F3H, DFR and PSY will be isolated and studied in the orchid species, Oncidium goldiana. The construction of antisense cassettes will also be carried out for CHS, DFR and PSY. RNA was isolated from various stages of Oncidium go/diana and its purity and concentration was determined. Partial genes of CHS (605bp), F3H (503bp), DFR (415bp) and PSY (543bp) was isolated from flower petals by RT-PCR using degenerate primers. A BLAST search for homology revealed that these sequences had high homology at both the amino and nucleic acid levels with other known plantThe temporal and spatial gene expression studies using semi-quantitative RT -PCR showed that F3H and DFR were floral specific and they had the highest expression at the yellow buds stage. The level of CHS was the highest in partially opened flowers and PSY was expressed at its highest levels in green buds. CHS and PSY were not floral specific as they were also present in leaves. The antisense cassettes were constructed for CHS, DFR and PSY. These vectors were driven by a 35S promoter and Nos 3' terminator sequence. The CHS vector was 13'480bp, the DFR was 13380bp and PSY was 13430bp. These antisense cassettes were suitable for transformation by biolistic gun bombardment or via Agrobacleriunt infection